Estimativa da densidade dos perfis de corpos celulares de neurônios em regiões corticais e hipocampais e avaliação comportamental de camundongos sob o uso de esteroides anabolizantes - Damião, Bruno (2014)
The use of AAS (Anabolic-Androgenic Steroids), currently known as steroids or “roids”, has increased in the last years due to a growing bid of faked products. This fact, allied to a low-quality scholarship, put Brazil among the most anabolic-drug consuming countries in the world. Because of their use-risk without medical follow-up these drugs has being studied extensively in order to clarify by empiric data their actual harmful effects or potential benefits when properly used. The present study analyzed the effects of two AAS, sold in Brazil as Winstrol Depot® (stanozolol) and Deposteron® (testosterone cypionate), upon neuronal loss by means of estimated profile analysis of neuron cell bodies density in three cortical areas (limbic, motor and sensorial) and three hippocampal areas (CA1, CA2 and CA3), besides a behavioral analysis searching for changes in parameters related to anxiety (Elevated Plus Maze – EPM), memory (Memory Analysis and Object Recognition Memory) and motor activity (Open Field). For the experiment, we used 60 Swiss mice, 30 males and 30 females, which were divided into three groups: control, Deposteron®-treated, and Winstrol Depot®-treated, each one composed by 20 animals, 10 males and 10 females. The animals received AAS or saline solution twice a week (on Tuesdays and Thursdays) and were put on 15-minute swimming exercises thrice a week (on Mondays, Wednesdays and Fridays) for 30 days. After experiment-ending, the specimens accomplished behavioral tests and were euthanized by halothane inhalation. Their brains were withdrawn and stored in 4% paraformaldehyde solution for 12 hours. Homotypic cross-sections samples from each brain’s middle area were taken in order to evaluate the areas concerning our study. The results showed that there was a reduction in the estimated profile analysis of neuron cell bodies density of all cortical and hippocampal areas in female mice treated with Deposteron® and in hippocampal areas (CA2 and CA3) of female mice treated with Winstrol Depot® when compared to control group. A reduction in the estimated profile analysis of neuron cell bodies density was also displayed in limbic and hippocampal CA1 areas of male mice in both ASS-treated groups. Behavioral tests revealed that there was an increase in parameters related to anxiety and apathetic behavior while there were no detectable changes concerning motor activity or memory in AAS-treated animals on both groups.